Parenting and Disciplinary Behavior on Elementary School Student Learning Outcomes - Ria Fajrin Rizqy Ana; Frita Devi Asriyanti; Leny Suryaning Astutik (LPPM Undiksha, 2024)
This research is motivated by the fact that many students still need to be more disciplined in obeying the rules. This research aims to analyze the influence of parenting patterns on student learning outcomes, the influence of disciplinary behavior on student learning outcomes, and the influence of parental parenting and corrective behavior on student learning outcomes. This research is quantitative research with a correlational type. The population in this study was all students, totaling 74 students. The sample in this study used the entire population. The data collection methods used are questionnaires and documentation. The data collection instrument uses a questionnaire sheet. Data analysis techniques use validity, reliability, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of data analysis show that, first, parental parenting influences student learning outcomes. Second, there is no influence of disciplinary behavior on student learning outcomes partially. Third, there is a simultaneous influence of parental parenting and corrective behavior on learning outcomes. It is concluded that good parenting and corrective behavior can improve the learning outcomes of elementary school students.